A Portuguese Treatise on the Plague: João Curvo Semedo's Tratado da Peste - Silva, Gabriel (2022)
João Curvo Semedo (1635-1719) is the author of, among other works, the Tratado da Peste (1680), a treatise concerning the origins and causes of the plague, and its prevention and treatment. This article aims to present this opus, which has long been neglected, to understand how it follows the tradition of the genre of 'plague literature', and to highlight its value and originality. This analysis draws upon other plague treatises, especially those written by Portuguese physicians.